Disengaging the engaged ones: gender-stereotyped tutoring systems are undermining self-efficacy and flow state of girls - Martins, Francys Rafael do Nascimento; Pinto, Ig Ibert Bittencourt Santana; Challco, Geiser Chalco; Isotani, Seiji; Sousa, Breno Felix de; Barbosa, Jessica Fernanda Silva; Reis, Marcelo (Anais Estendidos do Congresso Brasileiro de Informática na Educação (CBIE), 2023)
Gender Stereotyped design elements in gamification, such as using avatars aligned exclusively with the preferences of the male gender, may lead women not to develop their aptitudes or not perform adequately in male-prevalent groups, such as STEM fields (Science, Technology, Engineering, and Mathematics). This study aims to analyze the effects of stereotyped game elements in gamified tutoring systems on flow experience, self-efficacy, and learning performance. With this intent, we conducted an experimental study with Brazilian high school students. Findings indicated that stereotypes negatively affect the self-efficacy levels of female participants. Performance and flow experience levels were not affected by stereotypes. However, male participants were found to be more engaged (flow state) than women in the gamified tutoring system. These results suggest that educational technologies, such as tutoring systems and gamification, must have adaptable interfaces to avoid stereotyping and promote gender equity.